A 15-year Experience of Complex Scalp Reconstruction Using Free Tissue Transfer—Analysis of Risk Factors for Complications - Fischer, John P.; Sieber, Brady; Nelson, Jonas A.; Kovach, Stephen J.; Taylor, Jesse A.; Serletti, Joseph M.; Wu, Liza C.; Kanchwala, Suhail; Bartlett, Scott P.; Low, David W. (Journal of Reconstructive Microsurgery, 2013)
Purpose Large, complex scalp defects represent a significant reconstructive challenge, thus a variety of free tissue transfer techniques have been employed to optimally provide soft tissue coverage. The aim of this study is to determine factors associated with complications.Methods A retrospective cohort study was performed on patients undergoing free tissue transfer for scalp defects from 1997 to 2011. Patients were compared with respect to demographics, defect characteristics, intraoperative factors, flap choice, and postoperative complications.Results Forty-three flaps were performed in 37 patients with a success rate of 97.7%. Multivariate regression demonstrated that defect characteristics (size of defect) and patient-related factors (age and smoking) were associated with wound complications in scalp reconstruction. Outcomes were similar between the latissimus dorsi (LD) and anterolateral thigh (ALT) groups and the immediate cranioplasty patients with respect to all forms of complicationsConclusions We report a 98% success rate using free tissue transfer for complex scalp defects and identify defect size, patient age, and smoking as factors associated with wound complications. Patient comorbidities were associated with major complications. We report equal efficacy in using the ALT and LD, as well as immediate cranioplasty.Level of Evidence Prognostic/risk, level III
Keywords: scalp reconstruction; free flap; complications